Does therapeutic writing help people with long-term conditions? Systematic review, realist synthesis and economic considerations - Nyssen, O; Taylor, S; Wong, G; Steed, E; Bourke, L; Lord, J; Ross, C; Hayman, S; Field, V; Higgins, A; Greenhalgh, P; Meads, C (National Institute for Health Research, 2016)
Background Writing therapy to improve physical or mental health can take many forms. The most researched model of therapeutic writing (TW) is unfacilitated, individual expressive writing (written emotional disclosure). Facilitated writing activities are less widely researched. Data sources Databases including: MEDLINE, EMBASE, PsychINFO, Linguistics and Language Behavior Abstracts, AMED, and CINHAL were searched from inception to March 2013. Review methods Four TW practitioners provided expert advice. Study procedures were conducted by one reviewer and checked by a second. Randomised controlled trials (RCTs) and non-randomised comparative studies were included. Quality was appraised using the Cochrane risk of bias tool. Unfacilitated and facilitated TW studies were analysed separately under ICD-10 chapter headings. Meta-analyses were performed where possible using Revman 5.2. Costs were estimated from an NHS perspective and three cost-consequence case studies were prepared. Realist synthesis followed RAMESES guidelines. Objectives To review the clinical and cost-effectiveness of TW for people with long-term health conditions (LTCs) compared to no writing, or other controls, reporting any relevant clinical outcomes. To conduct a realist synthesis to understand how TW might work, and for whom. Results From 14,658 unique citations, 284 full text papers were reviewed and 64 studies (58 RCTs) were included in the final effectiveness reviews. Five studies examined facilitated TW, these were extremely heterogeneous with unclear or high risk of bias, but suggested that facilitated TW interventions may be beneficial in individual LTCs. Unfacilitated expressive writing was examined in 59 studies of variable, or unreported, quality. Overall there was very little or no evidence of any benefit reported in the following conditions(number of studies): HIV (six); breast cancer (eight); gynaecological and genitourinary cancers (five); mental health (five); asthma (four); psoriasis (three); chronic pain (four). In inflammatory arthropathies (six) there was a reduction in disease severity (n= 191, standardised mean difference (SMD) - 0.61 [95% confidence intervals (95% CI) -0.96, -0.26]) in the short term on meta-analysis of four studies. For all other LTCs there was either no, or sparse, data with no, or inconsistent, evidence of benefit. From 14,658 unique citations, 284 full text papers were reviewed and 64 studies (58 RCTs) were included in the final effectiveness reviews. Five studies examined facilitated TW, these were extremely heterogeneous with unclear or high risk of bias, but suggested that facilitated TW interventions may be beneficial in individual LTCs. Unfacilitated expressive writing was examined in 59 studies of variable, or unreported, quality. Overall there was very little or no evidence of any benefit reported in the following conditions(number of studies): HIV (six); breast cancer (eight); gynaecological and genitourinary cancers (five); mental health (five); asthma (four); psoriasis (three); chronic pain (four). In inflammatory arthropathies (six) there was a reduction in disease severity (n= 191, standardised mean difference (SMD) - 0.61 [95% confidence intervals (95% CI) -0.96, -0.26]) in the short term on meta-analysis of four studies. For all other LTCs there was either no, or sparse, data with no, or inconsistent, evidence of benefit. Realist review findings suggested that facilitated TW is a complex intervention and group interaction contributes to the perception of benefit. It was unclear from the available data who might benefit most from facilitated TW. Limitations Difficulties with developing realist review programme theory meant that mechanisms operating during TW remain obscure. Conclusions Overall there is little evidence to support the effectiveness or cost-effectiveness of unfacilitated expressive writing interventions in people with LTCs. Further research focussed on facilitated TW in people with LTCs could be informative.